Evaluation of intercropping elephant-foot yam (Amorphophallus paeoniifolius) with pulses for yield, economics, corm quality and soil health - G SUJA; R SARAVANAN; SREEKUMAR, J (Current Horticulture, 2025)
The field experiments were conducted at ICAR-Central Tuber Crops Research Institute, Thiruvananthapuram, Kerala, to assess the feasibility of intercropping elephant-foot yam [Amorphophallus paeoniifolius (Dennst.) Nicolson] with various pulse crops, during 2017-19. The factorial randomized block design with three elephant-foot yam varieties (Gajendra, Sree Padma and Sree Athira), three pulse crops [greengram, Vigna radiata (L.) R. Wilczek. (var. Co-Gg-7), blackgram, Vigna mungo (L.) Hepper (var. Co-6), and soybean, Glycine max (L.) Merr. (var. JS-95-60)], and two fertility levels. Averaging over two years, yield of elephant-foot yam under intercropping (32.82 t/ha) was comparable to sole cropping (35.90 t/ha), with a slight decrease of 8.58%. The combination of elephant-foot yam var. Gajendra + soybean under full fertility level resulted in higher yield (66.40 t/ha), corm equivalent yield (66.77 t/ha), production efficiency (247.30 kg/ha/day), equivalent energy (239.91 × 103 MJ/ha), net income (₹ 10, 09, 856/ha), B:C ratio (3.20) and added profit of ₹ 2,33,164/ha over sole cropping of elephant-foot yam var. Gajendra (46.48 t/ha, 172.45 kg/ha/ day, 167.33 × 103 MJ/ha). These intercropping systems did not adversely affect the soil chemical properties or biochemical constituents of corms, underscoring the viability of intercropping elephant-foot yam with pulses as a sustainable practice.